Researching Displaced Persons During COVID-19: Catering for Users’ Specific Needs in Media Accessibility Projects - Jiménez-Andrés, Maria; Alemam, Nourhan (Journal of Audiovisual Translation, 2021)
Coronavirus disease 2019 (COVID-19) has created additional barriers to human interactions. For those conducting research with displaced persons, the barriers posed by COVID-19 add up to the existing linguistic, cultural, geographical and ethical obstacles that this type of research involves. In most cases, researchers have resorted to technological solutions to bridge the communication gap caused by the pandemic. However, the heterogeneous profiles and disadvantaged circumstances of displaced persons require further considerations and planning. This paper examines the experiences of researchers conducting research with displaced persons during COVID. It outlines the special considerations taken and provides recommendations for those conducting research in similar contexts. The communities that engaged in this research were based in Greece, Poland, Italy, Lebanon and Spain. While the focus of the study is displaced persons, the insights presented can be of benefit to those conducting research with other vulnerable groups. Lay summary The COVID-19 pandemic has affected human interaction. Research often involves face-to-face contact with participants and other agents, which COVID-19 prevented. The mobility restrictions and safety regulations have difficulted data collection. Many processes have been moved online, but not everybody can interact successfully with technology i.e., some people do not have access to devices or internet, others do not have the skills required. Other barriers can be linguistic or cultural. Researchers must ensure that the research is safe and accessible to participants. This study presents how researchers working with migrants in the field of Media Accessibility have adapted their studies during COVID-19. The study reports on the results of a questionnaire distributed among researchers working on three projects conducted in European countries and Lebanon. The results show that more time was invested in data collection, and that flexibility and innovation were key to the success of the projects. The paper explains how researchers made data collection tools accessible to participants to ensure that participants could take part in the study. The considerations taken could be applied beyond the pandemic as it is adaptable to other research contexts, testing environments, diverse audiences, and disciplines.